Exploring the type of social support available to aged male hypertensive clients in Ghana - Zufaa James Konir; Ndiok Akon Emmanuel; Aboh Irene Korkoi; Wooley Philomina (Sciendo, 2022)
To explores the social support available to aged hypertensive male clients in a municipality in Ghana.